Recent progress on biological control of Fusarium wilt in vegetable crops - Feng Xiong; Mingfeng Guo; Yawen Liu; Xiaochen Liu; Jiahui Fu; JunZhu Gao; Man Yang; Rui Ma; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Crop Protection, 2026)

Digital twin modelling of shield tunneling undercrossing existing tunnels: A case study - Qiujing Pan; Yiming Zhang; Cong Tang; Weibo Luo; Zihan Yang; Mingfeng Lei (Tunnelling and Underground Space Technology, 2026)

Sample-level PRRSV RT-PCR prevalence in pigs in mainland China (2004–2025): A systematic review and meta-analysis - Mengke Si; Yiwei Wang; Xiang Li; Junxue Qiu; Xiaoyu Chong; Baolei Yang; Mingfeng Chu; Yuchen Liang; Wei Cheng; Jingyan Zhang; Xuelong Chen; Yanping Qi (Preventive Veterinary Medicine, 2026)

Wood-based aerogel with “micro screen” structure: employing multi-layers retention barriers for salt evaporation resistance and lithium adsorption - Mingfeng Dong; He Zhang; Zizheng Zhu; Tao Zhang; Dongya Yang; Fengxian Qiu (Desalination, 2026)

Interactions mechanisms decoding of macadamia protein isolate-procyanidins dimer complexes and synergistic effect for high internal phase Pickering emulsions stabilization - Tingting Chen; Zhipan Wang; Mingfeng Fang; Ming Zhang; Gangjun Guo; Liqing Du; Taotao Dai; Xixiang Shuai (Food Chemistry, 2026)

Electro–ultrasonic coupled for enhanced removal efficiency of toxic fine particles from biomass combustion: Performance optimization and synergistic mechanisms - Hailin Gu; Zhengcheng Lou; Mingfeng Lu; Jiaqi Ran; Xu Wang; Chengxu Tu; Guangxue Zhang; Fubing Bao (Journal of Hazardous Materials, 2026)

Multi-omics insights into key aroma compound formation during Chinese bayberry wine fermentation by Pichia kluyveri ZFM-0524 - Shuxun Liu; Mingfeng Cao; Yan Zhao; Yufeng Xu; Luan Zhang; Yuling Cai; Qing Gu (International Journal of Food Microbiology, 2026)

De novo transcriptome profiling reveals the bioeffect of the clam (Cyclina sinensis) to graded extremely low-frequency electromagnetic fields (ELF-EMF, 50 Hz) exposure - Mingming Zhang; Yuqing Fan; Mingfeng Zhu; Shouhai Liu; Hu Zhang; Chaojun Gu; Zhenyu Wang; Boping Yang; Guo Qiao (Environmental Pollution, 2026)

CFD-DEM simulations on the flow mechanisms and pressure transfer characteristics of foam-conditioned sands in a shield chamber - Daobing Zhang; Zheng Wang; Junqiu Ma; Qiujing Pan; Hao Xiong; Mingfeng Lei (Computers and Geotechnics, 2026)

Waste paper-spent coffee grounds synergistically derived carbonized cellulose aerogel for multifunctional phase change materials: Enhancing thermal energy storage, Joule/solar heating, and electromagnetic shielding - Lihang Yang; Yutao Wang; Mingfeng Chen; Dehao Li; Feng Wang; Liyuan Zhang; Yu Liang; Renjie Chen; Jun Li (Biomass and Bioenergy, 2026)

Numerical Investigation on the Mechanical Properties and Damage Mechanisms of Xiyu Conglomerate Under Freeze–Thaw Cycles - Yingming Xiao; Chaojun Jia; Mingfeng Lei; Ruifeng Pang; Qiang Zhang (Rock Mechanics and Rock Engineering, 2026)

Asparagus Polysaccharide Ameliorates TNF-α-Mediated MH7A Cell Dysfunction and Collagen-Induced Arthritis in Mice - Mingfeng Yang; Fangyan Xu; Bin Zhang; Lijun Xu (Cell Biochemistry and Biophysics, 2026)

Physics-informed neural network for predicting reaction kinetics of quinoline hydrodenitrogenation - Shihao Wang; Tao Li; Yuelin Xu; Wenbin Chen; Xiaoqian Dang; Wei Zhang; Chen Zhang; Cuiqing Li; Yong Luo; Feng Liu; Mingfeng Li (Fuel, 2026)

Impacts of extreme drought events on forest ecosystem resilience in mainland Southeast Asia - Lusha Ma; Kun Yang; Zongqi Peng; Run Sun; Mingfeng Zhang; Danni Su; Jingcong Ma; Yanhui Zhu; Xianchun Pan (Science Bulletin, 2026)

Corrigendum to ‘Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan’ [J. Environ. Chem. Eng. 13 (6) (2025) 120190] - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2026)

Tree-inspired solar interfacial evaporation: From isolated structural mimicry to integrated functional synergy - Zhicheng Xu; Xintao Zhou; Zhongqiu Luo; Mingfeng Zhong; Zhijie Zhang (Journal of Environmental Chemical Engineering, 2026)

Valorization of rice husk biochar as a dual-confined slow-release fertilizer: Synergistic effects of pore-throat constriction and active-site engineering - Yuyang Cong; Dongni Qiu; Jie Li; Mingfeng Wang; Donghai Wang; Zhiwen Chen; Ke Zhang (Journal of Environmental Chemical Engineering, 2026)

Characterization of Pichia pastoris protease and its application in improving the quality and storage stability of dried pork jerky - Ziyuan Zhang; Yuan Huang; Mengning Zhao; Yixin Zhang; Mingfeng Xu; Fangda Sun; Rongrong Yu (Food Chemistry, 2026)

Conjunctive analysis of BSA-Seq and KASP markers unveils the preliminary candidate genes controlling chalkiness of rice grain - Mingfeng Tang; Zhongwei Wang; Tingting Zeng; Tingting Fu; Wei Zhang; Yongchuan Huang; Yanjie Yao; Yongyang Fan; Xianwei Zhang (Euphytica, 2026)

Enhancement of macadamia protein solubility and functionality using combined pH-shift-heat treatment: Role of ionic environment (PBS vs water) - Xixiang Shuai; Mingfeng Fang; David Julian McClements; Tingting Chen; Zhipan Wang; Liqing Du; Ming Zhang; Wei Zhou; Taotao Dai; Jihua Li; Jun Chen (Food Chemistry, 2026)

Intercropping enhances soil organic carbon accumulation by modulating microbial interactions in saline-alkali soils - Lijun Zhang; Guixiang Zhou; Jiabao Zhang; Lin Chen; Congzhi Zhang; Donghao Ma; Hui Zhang; Jian Feng; Mingfeng Liu (Applied Soil Ecology, 2026)

Pea protein-steviol glycosides complexes: Fabrication, characterization and evaluation for the emulsifying capacity - Wen Wang; Jingyu Xia; Min Zhang; Enqi Pei; Cuina Wang; Mingfeng Xu; Rongrong Yu (Food Chemistry, 2026)

Evaluation of novel probiotic Bacillus candidates from the midgut of gibel carp (Carassius auratus gibelio): effects on fish growth, immunity, and resistance to CyHV-2 infection - Mingming Zhang; Ni Ma; Yaqin Yang; Mingfeng Zhu; Hu Zhang; Zhigang Zhao; Jialin Zhang; Mingzhu Pan; Zhitao Qi; Guo Qiao (Aquaculture International, 2026)

GNSS/MEMS INS tightly coupled algorithm for agricultural machinery navigation enhanced by random forest-based behavioral state awareness - Yihang Feng; Guanwen Huang; Mingfeng Wang; Xin Li; Zhenhong Li; Hang Li; Kai Zhang; Ce Jing (Computers and Electronics in Agriculture, 2026)

Optimizing harvest aid applications for mechanical cotton harvesting: A meta-analysis of defoliation–yield trade-offs driven by crop physiology and environmental factors - Zhenwang Zhang; Yukun Wang; Xinghua Yu; Keke Yu; Huijie Hou; Qinghua Liao; Kexin Li; Zhijie Shi; Jianxin Dong; Guodong Chen; Sumei Wan; Shanwei Lou; et al. (Field Crops Research, 2026)

Succession patterns, environmental connections, and assembly mechanisms of gut microbiota in the giant freshwater prawn (Macrobrachium rosenbergii) across lifespan - Songbao Zou; Yao Zheng; Julin Yuan; Meng Ni; Mei Liu; Dan Zhou; Qiang Gao; Mingfeng Deng; Ruichen Wang; Xin Zhang (Aquaculture, 2026)

CYP321A9 mediates the metabolism of two diamide insecticides, chlorantraniliprole and tetrachlorantraniliprole in Spodoptera frugiperda - Wenjing Cao; Mingfeng Huang; Yongheng Zhang; Meng Long; Xuesheng Li (Pesticide Biochemistry and Physiology, 2026)

Molten Li/Na/K ternary carbonate salt pyrolysis of biomass: A facile approach for co-production of porous biochar, CO-enriched syngas, and high-selectivity bio-oil - Jiazhen Tang; Tianyu Lu; Xing Xie; Dan Lin; Dongjing Liu; Qingfa Zhang; Mingfeng Wang; Weiwei Liu; Zhong Ma; Haiping Yang; Shihong Zhang; Bin Li (Journal of Cleaner Production, 2026)

A DFN–DEM approach to determine equivalent mechanical parameters of rock mass with different joint densities - Liang Wang; Shijie Zhou; Juan Huang; Mingfeng Lei; Yonggang Han; Jian Zhang; Chaojun Jia (Bulletin of Engineering Geology and the Environment, 2026)

Study on nitrogen and phosphorus adsorption from biogas slurry by biochars derived from different feedstocks - Jingjing Luo; Wenyu Jiang; Huan Ma; Mingfeng Wang; Qingfa Zhang; Bin Li; Weiwei Liu (Environment, Development and Sustainability, 2025)

Metabolic profiling of triptophenolide in rat plasma, urine, bile and faeces after intragastric administration - Mingfeng Jiang; Qiang Hou; Shuilian Wu; Xiaofan He; Tingting Zhang; Rongjing Zhou (Natural Product Research, 2025)

Study on nutrient release characteristics of infiltration biochar fertilizer coated by cross-linked chitosan - Pinghui Wei; Xinyuan Fu; Mingfeng Wang; Weiwei Liu; Qingfa Zhang; Bin Li; Zhong Ma (Journal of Environmental Chemical Engineering, 2025)

Insight into metal-support interactions of NiMo hydrodesulfurization catalysts and their variations during application - Wenhui He; Yanjuan Xiang; Mudi Xin; Weiming Zhai; Sicong Qiao; Nan Zhang; Limei Qiu; Siyang Yan; Feng Liu; Jianqiang Wang; Guangtong Xu; Jiaxu Liu; et al. (Chemical Engineering Journal, 2025)

Improving stability and UV protection properties of phycocyanin nanoparticle-based Pickering emulgels via amorphous cationic starch complexation - Yacheng Hao; Jiahao Mei; Dongfang Ling; Zhe Zhang; Sai Li; Zhiyong Gong; Xin Liu; Mingfeng Xu; Yilin Lin; Rongrong Yu (Carbohydrate Polymers, 2025)

Multivariate data analysis of a severe air pollution event in Shihezi city, China - Feifan Chen; Qing He; Zhujun Zhao; Zhongqi Lu; Mingfeng Yang; Gang Ren; Jin Wang; Hongwei Zhang; Dongliang An; Chunxia Wu (Atmospheric Pollution Research, 2025)

Morphology-Controlled Alumina-Supported MoS2 catalysts for enhancing hydrogenation and hydrodenitrogenation via metal clusters - Chenxi Li; Aiguo Zheng; Hong Nie; Wei Han; Mingfeng Li; Anpeng Hu; Le Zhang; Huifeng Li (Fuel, 2025)

Underlying mechanism of sucrose esters on myofibrillar protein O/W emulsion gel behaviour under different ionic strengths: Focus on emulsion characterisation, protein structural changes and molecular interactions - Xiang Li; Bo Wang; Wenwen Hou; Jie Tang; Hongbin Lin; Junqiang Lian; Qian Liu; Mingfeng Xu; Yuan Ma; Dong Yu; Dong Zhang; Jiaxin Chen (Food Chemistry, 2025)

Optimal planting density enhances cotton yield by coordinating boll–leaf system photosynthesis under heat-limited conditions - Minzhi Chen; Yinhua Yan; Peng Yan; Yali Zhang; Jingshan Tian; Mingfeng Yang; Chuangdao Jiang; Wangfeng Zhang (Field Crops Research, 2025)

Experimental Investigation on Triaxial Shear Property and Permeability of Concrete–Rock Interface Under Hydromechanical Coupling - Yanni Zheng; Sheng Zhang; Mingfeng Lei; Chenghua Shi; Zhinan Lin; Chaojun Jia (Rock Mechanics and Rock Engineering, 2025)

A bilayer hydrogel evaporator with vertical channel for desalination applications - Mingfeng Dong; Zizheng Zhu; Yuting Dai; Dongya Yang; Tao Zhang; Fengxian Qiu (Journal of Water Process Engineering, 2025)

Examining how green space patterns affect noise distribution in urban areas with varying built-up densities - Mingfeng Zhang; Yuanxiang Wu; Mengmeng Li; Qi Meng; Jian Kang (Journal of Environmental Management, 2025)

ACE-inhibitory peptides from Morchella esculenta: screening, kinetics, and molecular dynamics simulation - Wenjun Zeng; Xudong Yu; Mingfeng Chen; Huiling Zhang; Jucai Xu; Xiaofang Zeng; Ying Liang (Food Chemistry, 2025)

Synergistic effects of PGPR and organic fertilizer on soil fertility, enzyme activities, and microbial community composition in saline-alkali rice systems - Mingfeng Guo; Junzhu Gao; Man Yang; Yawen Liu; Jiahui Fu; Rui Ma; Feng Xiong; Tingyu Zhang; Xuesheng Liu; Yu Jin; Juanjuan Qu (Applied Soil Ecology, 2025)

Safety assessment of shield tunnel underpassing railway bridges considering coupled randomness of stratigraphy and tunneling parameters - Chenghua Shi; Xuanyu Zhang; Zixu Zhu; Tao Zhu; Mingfeng Lei; Xiaohe Sun (Tunnelling and Underground Space Technology, 2025)

Restoration of secondary forest in the Greater Mekong Subregion struggles to offset primary forest carbon losses - Zongqi Peng; Yanhui Zhu; Kun Yang; Yi Luo; Xixi Lu; Jiasheng Wang; Yang Zhang; Danni Su; Run Sun; Mingfeng Zhang; Jingcong Ma; Yang Liu; et al. (Global and Planetary Change, 2025)

Structure-performance relationship between zeolites properties and hydrocracking performance of tetralin over NiMo/Al2O3-Y catalysts: A machine-learning-assisted study - Wei Wang; Mingfeng Li; Yang Zhang; Kang Qin; Li Zhuang; Ping Yang; Hong Nie (Fuel, 2025)

Temperature effects on the micro-to-macro mechanical and creep properties of impurity salt rock - Chengxing Zhao; Cheng Lyu; Mingfeng Yang; Yunhui Zhang; Ping Zhou (Bulletin of Engineering Geology and the Environment, 2025)

Optimizing chemical topping in cotton: Effects of planting density and variety sensitivity to mepiquat chloride - Yanqin Wu; Chaoyuan Tang; Mingwei Du; Jingshan Tian; Mingfeng Yang; Yali Zhang; Wangfeng Zhang (Field Crops Research, 2025)

Promotion mechanism of rare-earth elements doping on performance of CaO/CeO2 sorbent for high temperature CO2 capture - Yunfeng Li; Jiarui Wu; Feng Liu; Weiwei Liu; Bin Li; Qingfa Zhang; Mingfeng Wang; Haiping Yang; Zhen Fang; Zhong Ma (Chemical Engineering Journal, 2025)

Cellulose-based photo-curable chiral nematic ink for direct-ink-writing 3D printing - Mingfeng Wu; Huan Wang; Afroza Akter Liza; Lukuan Guo; Wenyuan Zhu; Junlong Song; Fengshan Zhang; Yanshao Liu; Yongcan Jin; Jiaqi Guo (Carbohydrate Polymers, 2025)

Dapagliflozin promotes browning of white adipose tissue through the FGFR1-LKB1-AMPK signaling pathway - Yue Lv; Chengrui Zhao; Qiuyan Jiang; Yilin Rong; Mingfeng Ma; Lili Liang; Weiping Li; Jiuxuan Zhang; Ning Xu; Huiwen Wu (Molecular Biology Reports, 2024)
Background Obesity is associated with a wide variety of metabolic disorders that impose significant burdens on patients and society. The “browning” phenomenon in white adipose tissue (WAT) has emerged as a promising therapeutic strategy to combat metabolic disturbances. However, though the anti-diabetic drug dapagliflozin (DAPA) is thought to promote “browning,” the specific mechanism of this was previously unclear. Methods In this study, C57BL/6 J male mice were used to establish an obesity model by high-fat diet feeding, and 3T3-L1 cells were used to induce mature adipocytes and to explore the role and mechanism of DAPA in “browning” through a combination of in vitro and in vivo experiments. Results The results show that DAPA promotes WAT "browning" and improves metabolic disorders. Furthermore, we discovered that DAPA activated "browning" through the fibroblast growth factor receptors 1-liver kinase B1-adenosine monophosphate-activated protein kinase signaling pathway. Conclusion These findings provide a rational basis for the use of DAPA in treating obesity by promoting the browning of white adipose tissue.

Nitrogen Doping Engineering of V2CTx based Zinc Ion Hybrid Microcapacitors with Quadruple High Energy Density - Wei Lai; Sairao Zhao; Mengdi Guo; Di Wu; Shijun Luo; Chuankun Zhang; Tao Huang; Wenbin He; Mingfeng Li; Xin Zhou; Xiao Luo; Jian Li; et al. (Chemical Engineering Journal, 2024)

Experimental Investigation on Freeze–Thaw Damage Mechanism of Xiyu Conglomerate Under Uniaxial Cyclic Loading - Chaojun Jia; Ruifeng Pang; Qiang Zhang; Mingfeng Lei; Chenghua Shi; Wenxin Li (Rock Mechanics and Rock Engineering, 2024)

Optimizing radiation capture in machine-harvested cotton: A functional-structural plant modelling approach to chemical vs. manual topping strategies - Shenghao Gu; Shuai Sun; Xuejiao Wang; Sen Wang; Mingfeng Yang; Jie Li; Paerhati Maimaiti; Wopke van der Werf; Jochem B. Evers; Lizhen Zhang (Field Crops Research, 2024)

In situ tracking of the impact of atomic-scale fragment structures on MoS2 nanocrystals for high-stability industrial NiMo/γ-Al2O3 hydrodesulfurization catalysts - Wenhui He; Mudi Xin; Yanjuan Xiang; Weiming Zhai; Zheng Chen; Limei Qiu; Aiguo Zheng; Feng Liu; Le Zhang; Guangtong Xu; Mingfeng Li (Chemical Engineering Journal, 2024)

Dynamic response of a transmission conductor following delayed ice shedding by reduced-scale model test - Yuelong Zhang; Yong Guo; Wenjuan Lou; Weizheng Zhou; Mingfeng Huang (Cold Regions Science and Technology, 2024)

Geochemical characteristics, Li source and genesis mechanism of thermal mineral water in Sichuan Basin, SW China - Guosen Lv; Yunhui Zhang; Jiawei Liu; Mingfeng Yang; Si Wang (Geothermics, 2024)

Scalable recovery of polyhydroxyalkanoate (PHA) from a mixed microbial culture via a novel acidification-NaClO digestion process - Yi Zhang; Yuqi Zou; Qiuyue Tao; Mingfeng Yang; Marie Harder; Han Wang; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos (Bioresource Technology Reports, 2024)

Dynamic Analysis of Crane Vessel and Floating Wind Turbine during Temporary Berthing for Offshore On-Site Maintenance Operations - Jinkun Shi; Mingfeng Hu; Yifan Zhang; Xiaodong Chen; Sheng Yang; Thiago S. Hallak; Mingsheng Chen (Journal of Marine Science and Engineering, 2024)
With the increased scale and deployment of floating wind turbines in deep sea environments, jack-up installation vessels are unable to conduct maintenance operations due to limitations in water depth. This has led to the recognition of the advantages of floating cranes in offshore maintenance activities. However, the dynamic coupling between the crane and the floating wind turbine under wave and wind action can result in complex responses, which also relate to complex mooring configurations. The ability to maintain stability during maintenance operations has become a primary concern. In order to address this issue, a method of connecting a floating crane with a floating wind turbine is proposed, simulating the berthing of a floating offshore wind turbine (FOWT) to a crane. Thus, a systematic comparison was conducted with frequency- and time-domain simulation using ANSYS-AQWA software. The simulation results demonstrated the feasibility and dynamic efficiency of this novel berthing approach. Connecting the crane vessel to a floating wind turbine significantly reduced the crane tip movement. Simulations showed that the crane tip movement in the X-, Y-, and Z-directions was reduced by over 30%, which implies that it may be feasible to conduct offshore on-site maintenance operations for the FOWT by using floating crane vessels if the two bodies were properly constrained.

Coupling and synergistic relationships between soil aggregate stability and nutrient stoichiometric characteristics under different microtopographies on karst rocky desertification slopes - Mingfeng Bi; Shuaipu Zhang; Qinxue Xu; Senzheng Hou; Mengwei Han; Xinrui Yu (CATENA, 2024)

SP94 engineered erythrocyte membrane enhanced the targeted delivery of biomimetic nanosuspension with IDO immunotherapy and chemotherapy in liver cancer - Faisal Raza; Liangdi Jiang; Shulei Zhang; Hajra Zafar; Yujiao Qiu; Jing Su; Mingfeng Qiu (Chemical Engineering Journal, 2024)

Comparison of batch, fed-batch and continuous operation modes for scalable polyhydroxyalkanoate (PHA) production and carbon sequestration from phenol - Qiuyue Tao; Heyun Huang; Mingfeng Yang; Yuqi Zou; Marie K. Harder; Qun Yan; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos; Yi Zhang (Journal of Water Process Engineering, 2024)

Zero-valent iron (nZVI) nanoparticles mediate SlERF1 expression to enhance cadmium stress tolerance in tomato - Ali Anwar; Yudan Wang; Mengqing Chen; Shuaiwei Zhang; Jinmiao Wang; Yunqiang Feng; Yanxu Xue; Mingfeng Zhao; Wei Su; Riyuan Chen; Shiwei Song (Journal of Hazardous Materials, 2024)

Cotton crop transpiration reveals opportunities to reduce yield loss when applying defoliants for efficient mechanical harvesting - Yongfan Chen; Jochem B. Evers; Mingfeng Yang; Xuejiao Wang; Zeshan Zhang; Shuai Sun; Yutong Zhang; Sen Wang; Fen Ji; Dao Xiang; Jie Li; Chunrong Ji; et al. (Field Crops Research, 2024)

A new strategy for enhanced phosphate removal from waters using ferric oxide impregnated biochar - Lili Dong; Yan Li; Xinli Wen; Mingfeng Zhao; Le Zhang; Mengmeng Zhu; Shunli Wan (Chemical Engineering Journal, 2024)

Influence of large-scale climate indices and regional meteorological elements on drought characteristics in the Luanhe River Basin - Min Li; Zilong Feng; Mingfeng Zhang; Yuhang Yao (Atmospheric Research, 2024)

Effective reduction of hydrogen consumption in ultra-deep hydrodesulfurization of diesel: Deep insights into the effect of thermodynamic limitations during hydrotreating - Yubai Zhang; Feng Liu; Wenbin Chen; Wei Han; Weiming Zhai; Yutao Lu; Mingfeng Li (Fuel, 2024)

Separation of spring viraemia of carp virus from large-volume samples using immunomagnetic beads - Jing Hongli; Zhang Min; Gao Longying; Si Liegang; Wang Na; Ge Mingfeng; Xu Shengwei; Wang Jianping; Wu Shaoqiang (Archives of Virology, 2024)

S-dinotefuran affects the social behavior of honeybees (Apis mellifera)and increases their risk in the colony - Fu Zhang; Wenjing Cao; Yongheng Zhang; Jie Luo; Jiangan Hou; Lichao Chen; Guoqiang Yi; Honghong Li; Mingfeng Huang; Linxi Dong; Xuesheng Li (Pesticide Biochemistry and Physiology, 2023)

A novel approach to achieving more efficient production of the mature form of human IL-37 in plants - Yao Zhang; Nadiyah Alqazlan; Zihe Meng; Jingyao Zhao; Nan Liu; Yuxin Zhang; Mingfeng Feng; Shengwu Ma; Aoxue Wang (Transgenic Research, 2023)

Understanding the curing kinetics of boron-based hyperbranched polysiloxane reinforced and toughened epoxy resin by rheology - Huawei Qiao; Mingfeng Chen; Bing Chen; Huagui Zhang; Botuo Zheng (Chemical Engineering Journal, 2023)

Experimental and DEM simulations of the mechanical properties of rock under freeze–thaw cycles - Jun Yu; Qiang Zhang; Chaojun Jia; Mingfeng Lei; Chenyang Zhao; Ruifeng Pang; Zong Li; Tao Zeng (Cold Regions Science and Technology, 2023)

Machine Learning-Based Prediction of Dynamic Responses of a Tower Crane under Strong Coastal Winds - Qiang Li; Weijie Fan; Mingfeng Huang; Heng Jin; Jun Zhang; Jiaxing Ma (Journal of Marine Science and Engineering, 2023)
With the rapid development of the construction industry, tower cranes are increasingly used in coastal engineering. However, due to the complexity of their operating environment, tower cranes are vulnerable to typhoons, thunderstorms, and other extreme natural disasters. Therefore, it is becoming increasingly important to carry out safety warnings for the tower crane structure under the action of strong winds. In this paper, a real-time monitoring system for tower responses based on the Internet of things (IoT), which realizes long-term monitoring of the whole process of tower crane operation, was built. Based on the long-term monitoring data and the machine learning algorithm, two tower response prediction models were established. During the transit of super typhoon In-fa, the maximum displacement of the tower structure was predicted in advance, based on the measured wind speed data at the site, which is in good agreement with the displacement data monitored by the IoT. The results show that under strong winds, the non-working tower has a response lag, resulting in the fact that its maximum displacement does not correspond to the maximum wind speed moment at the site. This is mainly due to the weathercock effect of the tower in the non-working condition. The prediction model proposed in this paper can provide timely and effective safety warnings for the tower structure. It also can provide useful engineering references and scientific structural safety warning suggestions for the same type of tower cranes that do not have IoT monitoring systems installed.

Nitrogen Application Promotes Drought-Stressed Sugar Beet Growth by Improving Photosynthesis, Osmoregulation, and Antioxidant Defense - Hongliang Zhou; Pengjie Xu; Lijuan Zhang; Ruimin Huang; Mingfeng Yang; Kaiyong Wang; Hua Fan (Journal of Soil Science and Plant Nutrition, 2023)

Overexpressing 4-coumaroyl-CoA ligase and stilbene synthase fusion genes in red raspberry plants leads to resveratrol accumulation and improved resistance against Botrytis cinerea - Junxin Zhang; Xihuan Yan; Tiran Huang; Huan Liu; Fang Liu; Meixia Yang; MingFeng Yang; Lanqing Ma (Journal of Plant Biochemistry and Biotechnology, 2023)

Precursors and formation pathways of furfural in sugarcane juice during thermal treatment - Huimei Huang; Jiebo Chen; Mingfeng Zheng; Lulu Zhang; Hongfei Ji; Huajin Cao; Fengxia Dai; Lu Wang (Food Chemistry, 2023)

Improved analytical solution for ground movements induced by circular tunnel excavation based on ground loss correction - Binbin Zhu; Peng Zhang; Mingfeng Lei; Lichuan Wang; Lun Gong; Chenjie Gong; Fudong Chen (Tunnelling and Underground Space Technology, 2023)

Recovery of polyhydroxyalkanoates (PHAs) polymers from a mixed microbial culture through combined ultrasonic disruption and alkaline digestion - Yuqi Zou; Mingfeng Yang; Qiuyue Tao; Keliang Zhu; Xiang Liu; Chunli Wan; Marie K. Harder; Qun Yan; Bo Liang; Ioanna Ntaikou; Georgia Antonopoulou; Gerasimos Lyberatos; et al. (Journal of Environmental Management, 2023)

Water footprint modeling and forecasting of cassava based on different artificial intelligence algorithms in Guangxi, China - Mingfeng Tao; Tingting Zhang; Xiaomin Xie; Xiaojing Liang (Journal of Cleaner Production, 2023)

Effects of Microplastics on the Mineral Elements Absorption and Accumulation in Hydroponic Rice Seedlings (Oryza sativa L.) - Mingfeng Tang; Yongchuang Huang; Wei Zhang; Tingting Fu; Tingting Zeng; Yongdong Huang; Xiaoxia Yang (Bulletin of Environmental Contamination and Toxicology, 2022)

Behaviour of electroosmotic consolidation by electrode configuration and fracture grouting - Yunguo Du; Chao Zhang; Changfei Gou; Wenwen Wu; Xiaobing Li; Xiuqing Hu; Wang Chaoliang; Li Mingfeng (Marine Georesources & Geotechnology, 2022)

The effects of initial deviatoric stress on anisotropy of marine clay and strain components - Heng Zhuang; Mingfeng Li; Chaoliang Wang; Lin Guo; Dikang Zhang; Hongke Du; Yunguo Du (Marine Georesources & Geotechnology, 2021)

Behaviour of thick marine deposits subjected to vacuum combined with surcharge preloading - Dikang Zhang; Hongtao Fu; Jun Wang; Dongqi Zhu; Xiuqing Hu; Yunguo Du; Changfei Gou; Chaoliang Wang; Mingfeng Li; Hai Wu (Marine Georesources & Geotechnology, 2021)

Carbonyl Reductase 1 Attenuates Ischemic Brain Injury by Reducing Oxidative Stress and Neuroinflammation - Leilei Mao; Kun Wang; Pengjie Zhang; Shihao Ren; Jingyi Sun; Mingfeng Yang; Feng Zhang; Baoliang Sun (Translational Stroke Research, 2021)

Anisotropic properties of shale and its impact on underground structures: an experimental and numerical simulation - Chaojun Jia; Qiang Zhang; Mingfeng Lei; Yanni Zheng; Juan Huang; Lichuan Wang (Bulletin of Engineering Geology and the Environment, 2021)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Identification of Prognostic Signatures of Alternative Splicing in Glioma - Yu Zeng; Peidong Zhang; Xizhao Wang; Ke Wang; Mingfeng Zhou; Hao Long; Jie Lin; Zhiyong Wu; Liang Gao; Ye Song (Journal of Molecular Neuroscience, 2020)

Improved robust tensor principal component analysis for accelerating dynamic MR imaging reconstruction - Mingfeng Jiang; Qiannan Shen; Yang Li; Xiaocheng Yang; Jucheng Zhang; Yaming Wang; Ling Xia (Medical & Biological Engineering & Computing, 2020)

Debris flows originating from colluvium deposits in hollow regions during a heavy storm process in Taining, southeastern China - Yong Zhang; Ningsheng Chen; Mei Liu; Tao Wang; Mingfeng Deng; Kanglin Wu; Binish Raj Khanal (Landslides, 2020)

Evaluating the dual porosity of landfilled municipal solid waste - Wenjie Zhang; Mingfeng Lin (Environmental Science and Pollution Research, 2019)

Overexpressing fusion proteins of 4-coumaroyl-CoA ligase (4CL) and stilbene synthase (STS) in tobacco plants leading to resveratrol accumulation and improved stress tolerance - Xuancheng He; Feiyan Xue; Lulu Zhang; Huili Guo; Lanqing Ma; Mingfeng Yang (Plant Biotechnology Reports, 2018)

Rhizobia promote the growth of rice shoots by targeting cell signaling, division and expansion - Qingqing Wu; Xianjun Peng; Mingfeng Yang; Wenpeng Zhang; Frank B. Dazzo; Norman Uphoff; Yuxiang Jing; Shihua Shen (Plant Molecular Biology, 2018)

Instability Mode Analysis of Surrounding Rocks in Tunnel Blasting Construction with Thin Bedrock Roofs - E. Deng; Weichao Yang; Mingfeng Lei; Rongshen Yin; Pingping Zhang (Geotechnical and Geological Engineering, 2018)

Design, synthesis, and SAR study of highly potent, selective, irreversible covalent JAK3 inhibitors - Linhong He; Mingfeng Shao; Taijin Wang; Tingxuan Lan; Chufeng Zhang; Lijuan Chen (Molecular Diversity, 2018)

Toward Improved Calibration of SWAT Using Season-Based Multi-Objective Optimization: a Case Study in the Jinjiang Basin in Southeastern China - Ying Chen; Xingwei Chen; Chong-Yu Xu; Mingfeng Zhang; Meibing Liu; Lu Gao (Water Resources Management, 2018)

Exudate components exert different influences on microbially mediated C losses in simulated rhizosphere soils of a spruce plantation - Yuanshuang Yuan; Wenqiang Zhao; Juan Xiao; Ziliang Zhang; Mingfeng Qiao; Qing Liu; Huajun Yin (Plant and Soil, 2017)

Vibratory Influential Zoning for Grade-Separated Tunnels Under the Load of Trains - Weichao Yang; Rongshen Yin; Mingfeng Lei; E. Deng; Pingping Zhang (Geotechnical and Geological Engineering, 2017)

CD19+ Tim-1+ B cells are decreased and negatively correlated with disease severity in Myasthenia Gravis patients - Yong Zhang; Xiuying Zhang; Yan Xia; Xiao Jia; Hao Li; Yanyan Zhang; Zhen Shao; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; et al. (Immunologic Research, 2016)

Lipid desaturation in prokaryotic pathway abates the high-oleic phenotype of FAD2-silenced tobacco at lower temperature - Lulu Zhang; Heshu Lu; Chunmei Liu; Feiyan Xue; Jing Yang; Lanqing Ma; Mingfeng Yang (Journal of Plant Biochemistry and Biotechnology, 2016)

TIPE2 Play a Negative Role in TLR4-Mediated Autoimmune T Helper 17 Cell Responses in Patients with Myasthenia Gravis - Yong Zhang; Zhen Shao; Xiuying Zhang; Xiao Jia; Yan Xia; Yanyan Zhang; Ning Xin; Mingfeng Guo; Jing Chen; ShuangShuang Zheng; YuZhong Wang; Linlin Fu; et al. (Journal of Neuroimmune Pharmacology, 2015)

Erratum to: The effect of functional forms of nitrogen on fuel-NO x emissions - Linghui Zhang; Dagen Su; Mingfeng Zhong (Environmental Monitoring and Assessment, 2015)

The effect of functional forms of nitrogen on fuel-NO x emissions - Linghui Zhang; Dagen Su; Mingfeng Zhong (Environmental Monitoring and Assessment, 2015)

Serpentinization, abiogenic organic compounds, and deep life - XianBin Wang; ZiYuan Ouyang; ShengGuang Zhuo; MingFeng Zhang; GuoDong Zheng; YongLi Wang (Science China Earth Sciences, 2014)

A genome-wide association study of severe teenage acne in European Americans - Mingfeng Zhang; Abrar A. Qureshi; David J. Hunter; Jiali Han (Human Genetics, 2014)

Obesity-related genetic variants, human pigmentation, and risk of melanoma - Xin Li; Liming Liang; Mingfeng Zhang; Fengju Song; Hongmei Nan; Li-E Wang; Qingyi Wei; Jeffrey E. Lee; Christopher I. Amos; Abrar A. Qureshi; Jiali Han (Human Genetics, 2013)

Interfering growth of malignant melanoma with Ang2-siRNA - Biao Wang; Zhaoliang Liu; Mingfeng Zhang; Xiuying San; Yanding Zhang; Weiqiang Zhang; Meishui Wang (Molecular Biology Reports, 2013)

PDGF-induced airway smooth muscle proliferation is associated with Human antigen R activation and could be weakened by AMPK activation - Pengju Zhang; Mingfeng Cao; Yi Liu; Zhimei Lv; Qingrui Yang; Xiaoyan Lin; Huaichen Li; Qiang Wan (Molecular Biology Reports, 2012)

Integrating pathway analysis and genetics of gene expression for genome-wide association study of basal cell carcinoma - Mingfeng Zhang; Liming Liang; Nilesh Morar; Anna L. Dixon; G. Mark Lathrop; Jun Ding; Miriam F. Moffatt; William O. C. Cookson; Peter Kraft; Abrar A. Qureshi; Jiali Han (Human Genetics, 2012)

Expression of SHH signaling pathway components in the developing human lung - Mingfeng Zhang; Hong Wang; Hongqi Teng; Jueping Shi; Yanding Zhang (Histochemistry and Cell Biology, 2010)

A high-density intervarietal map of the wheat genome enriched with markers derived from expressed sequence tags - Shulin Xue; Zhengzhi Zhang; Feng Lin; Zhongxin Kong; Yong Cao; Chunjun Li; Hongying Yi; Mingfeng Mei; Huilan Zhu; Jizhong Wu; Haibin Xu; Dongmei Zhao; et al. (Theoretical and Applied Genetics, 2008)

Induction and Characterization of Adventitious Roots Directly from the Explants of Panax notoginseng - Xianfu Gao; Chunbao Zhu; Wei Jia; Wenyuan Gao; Mingfeng Qiu; Yongyu Zhang; Peigen Xiao (Biotechnology Letters, 2005)

The effects of La(III) on the peroxidation of membrane lipids in wheat seedling leaves under osmotic stress - Fuli Zeng; Yi An; Hongtao Zhang; Mingfeng Zhang (Biological Trace Element Research, 1999)